On‐Line Control of Glucose Concentration in High‐Yielding Mammalian Cell Cultures Enabled Through Oxygen Transfer Rate Measurements. Issue 4 (10th January 2018) - Goldrick, Stephen; Lee, Kenneth; Spencer, Christopher; Holmes, William; Kuiper, Marcel; Turner, Richard; Farid, Suzanne S.
Abstract : Glucose control is vital to ensure consistent growth and protein production in mammalian cell cultures. The typical fed‐batch glucose control strategy involving bolus glucose additions based on infrequent off‐line daily samples results in cells experiencing significant glucose concentration fluctuations that can influence product quality and growth. This study proposes an on‐line method to control and manipulate glucose utilizing readily available process measurements. The method generates a correlation between the cumulative oxygen transfer rate and the cumulative glucose consumed. This correlation generates an on‐line prediction of glucose that has been successfully incorporated into a control algorithm manipulating the glucose feed‐rate. This advanced process control (APC) strategy enables the glucose concentration to be maintained at an adjustable set‐point and has been found to significantly reduce the deviation in glucose concentration in comparison to conventional operation. This method has been validated to produce various therapeutic proteins across cell lines with different glucose consumption demands and is successfully demonstrated on micro (15 mL), laboratory (7 L), and pilot (50 L) scale systems. This novel APC strategy is simple to implement and offers the potential to significantly enhance the glucose control strategy for scales spanning micro‐scale systems through to full scale industrial bioreactors. Abstract : This paper describes a novel on‐line glucose advanced process control (APC) strategy demonstrated to enhance glucose control for high‐yielding mammalian cell cultures. The described APC strategy is successfully implemented across multiple scales ranging from 15 mL (AMBR TM ‐15 system) to 50 L bioreactors. Furthermore, the method is highly robust and is demonstrated to control the glucose concentration across multiple mammalian cell lines with highly varied glucose uptake rates. Furthermore, the methodology utilizes routinely recorded measurements and is therefore highly applicable across all bioreactors regardless of scale or set up.